Smoothing the energy transfer pathway in quasi-2D perovskite films using methanesulfonate leads to highly efficient light-emitting devices - Kong, Lingmei; Zhang, Xiaoyu; Li, Yunguo; Wang, Haoran; Jiang, Yuanzhi; Wang, Sheng; You, Mengqing; Zhang, Chengxi; Zhang, Ting; Kershaw, Stephen V.; Zheng, Weitao; Yang, Yingguo; et al. (Nature communications, 2021)
Quasi-two-dimensional (quasi-2D) Ruddlesden–Popper (RP) perovskites such as BA 2 Cs n –1 Pb n Br 3 n +1 (BA = butylammonium, n > 1) are promising emitters, but their electroluminescence performance is limited by a severe non-radiative recombination during the energy transfer process. Here, we make use of methanesulfonate (MeS) that can interact with the spacer BA cations via strong hydrogen bonding interaction to reconstruct the quasi-2D perovskite structure, which increases the energy acceptor-to-donor ratio and enhances the energy transfer in perovskite films, thus improving the light emission efficiency. MeS additives also lower the defect density in RP perovskites, which is due to the elimination of uncoordinated Pb 2+ by the electron-rich Lewis base MeS and the weakened adsorbate blocking effect. As a result, green light-emitting diodes fabricated using these quasi-2D RP perovskite films reach current efficiency of 63 cd A −1 and 20.5% external quantum efficiency, which are the best reported performance for devices based on quasi-2D perovskites so far. Owing to large exciton binding energy, quasi-2D perovskite is promising for light-emitting application, yet inhomogeneous phases distribution limits the potential. Here, the authors improve the performance by using MeS additive to regulate the phase distribution and to reduce defect density in the films.